ANTIBACTERIAL ACTIVITY FOR BIOSURFACTANT PRODUCED BY STREPTOMYCES SPP. ISOLATED FROM SOIL SAMPLES - AL-HULU, SAMER M. (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The goal of the present study on isolation Streptomyces from soil samples with biosurfactant activity and antibacterial activity analysis. Methods: (25) The soil samples were taken form Hilla city. (10) It is Streptomyces spp. They were identified. (4) Streptomyces spp. having the ability to hemolysis on blood agar that has the capacity to generate biosurfactants. Streptomyces spp. 8 displayed a high degree of activity by having a blood agar inhibition zone (25 mm). Results: Antibacterial activity was evaluated for Streptomyces spp. 8 (Staphylococcus aureus, Escherichia Coli, and Pseudomonas aeruginosa). Streptomyces spp. 8 has greatest inhibition zone against S. aureus equal to 14 mm compared 12 mm against E. coli and 8 mm for P. aeruginosa. This Streptomyces spp. 8 characteristic was tested, it showed Gram positive with aerial mycelium gray in color on yeast malt extract agar. Negative for melanin produced on tyrosine broth medium, negative for H2S output, and pigment development, it has for the use of mannitol sucrose, glucose, and fructose as carbon source and negative for xylose. Conclusion: Isolated Streptomyces spp. having the potential to generate biosurfactants with antibacterial activity.